TRANSLATING THE “PREPOSITION + WHICH” CONSTRUCTION IN ENGLISH LEGAL TEXTS INTO INDONESIAN - Jaya, Doni (Paradigma: Jurnal Kajian Budaya, 2025)
Legal text translation is challenging because of its emphasis on semantic and syntactic faithfulness, while ST structures do not always have correspondent TL equivalents. One of such structures is the English “preposition + which” (PW) construction. This construction can be difficult to translate into Indonesian because the language does not always have ready-to-use connectors to produce a structurally faithful translation, often forcing translators to take the easy way of using ungrammatical and unnatural connectors which becomes the hallmark of the Indonesian legalese style. This research seeks to examine various ways to translate PW constructions in a more grammatical and natural way, which involves some degree of creative modification, as an alternative to the legalese style. This research is prescriptive in nature because it aims to promote the use of more natural and reader friendly style without sacrificing accuracy. Data in the form of English sentences containing various PW constructions were collected from several legal documents and then translated using the “legalese” and “creative” style for comparison purposes. The data contain various PW connectors such as in which, on which, at which, of which, to which, from which, by which, for which, under which, with which, without which, during which, and beyond which. The creative versions were then analyzed and discussed to generate a set of strategies to translate PW constructions, resulting in six major strategies and at least ten minor strategies which can be applied in combination with each other to produce accurate, natural, and grammatical translations. These findings are expected to reveal the complexity of PW construction translation and to help future translators to deal with similar STs.